Operationalizing reflection in experience-based workplace learning: a hybrid approach. Issue 1 (1st January 2020) - Justice, Sean B.; Bang, April; Lundgren, Henriette; Marsick, Victoria J.; Poell, Rob F.; Yorks, Lyle
ABSTRACT: This article explores the pragmatics of operationalizing reflection in experience-based workplace learning. It proposes a constructivist-situative framework – not typically considered feasible – based on balancing the complementary strengths of each individual framework. We distinguish among four empirically demonstrated approaches that operationalize reflection using one or the other framework: cognitive process approach; integration of critically reflective work behaviours; use of phenomenological critical incidents to review emotionally laden experiences; and situated exploration of interactions between individuals and tools. Next, we apply these four approaches to previously collected data from medical and managerial workplace learning contexts. Through secondary analysis, we explore the utility of a combined framework, and consider the challenges therein. We argue that operationalizing reflection based on complementarity looks feasible though challenging. We close by discussing the practice of researching reflection through reflection, and speculating on opportunities for future workplace learning research based on emerging redefinitions of workplaces, interventionist methodologies, and conceptualizing learning environments as sociomaterial.